A proteção contra a dispensa arbitrária como direito fundamental - Bortolon, Mariana Cavarra (2009)
This paper demonstrates that the employees protection against arbitrary dispensation in Brazil it shows unsatisfactory, due to inadequate interpretation that has been given to the art. 7, I of CF/88, combined with the inertia of the ordinary legislature to regulate the norm in question. To achieve the intended purpose, this study explains the stages of development of human labor in modernity, highlighting the rise of the value given to work in industrial capitalism and its consequent crisis, facing a scenario permeated by post-industrial capitalist model, characterized by the use of high technology. With this critical analysis of the work history in the modern period, demand reveal ways to revitalize the labor movement so that it will act as an agent of social emancipation, returning to the role of labor instrument guarantor of citizenship and human dignity. That said, is in order to defend the labor social rights as a fundamental right, essential step to understand the core problem of this study, which revolves around the art. 7, I of CF/88. Since then, it will begin an effort to understand how the employee protection against arbitrary or waiver without cause was developed in the domestic legal system, culminating with the analysis of the discussions held in the Constituent Assembly of 1987, which led to the art. 7, I of CF/88. At this moment, it starts to check the nuances of the rule in comment to clarify the interpretation of dominant nation doctrine on this standard, as well as the most appropriate interpretation of that article, according to a reading integrated with the other fundamental rights enshrined in the Constitution of 1988. In this perspective, in view of the inertia of the ordinary legislature to regulate this matter, it becomes to expose the limits that it should meet, taking into account the appreciation of the work as the foundation of the Republic and the implicit principle of social setback prohibition. Finally, the work is concluded by presenting an emancipator proposal to protect the employee against arbitrary dispensation in Brazil, which is able to curb corporate abuses and curb the intense process of unemployment and labor turnover.